الشخصیة الھامشیة لدى طالبات المرحلة المتوسطة - ھبة احمد مھدي, (مجلة الفتح للبحوث التربوية والنفسية, 2023)
ملخص البحث : تتجلى أھمیة البحث الحالي في أھمیة مرحلة المراھقة التي تقابلھا مرحلة المدرسة المتوسѧѧطة ، ففѧѧي ھѧѧذه المرحلѧѧة تكѧѧون المراھقѧѧات شѧѧدیدات الرغبѧѧة فѧѧي ولѧѧوج عѧѧالم الراشѧدین قبѧل التѧѧزود بѧالخبرة لمواجھѧѧة مواقѧف الحیѧѧاة المختلفѧة التѧѧي تتطلѧب مѧѧنھم اسѧѧتعدادا كافیѧѧا قبѧѧل دخѧѧولھم المرحلѧѧة الجدیѧѧدة ،. ھѧѧدف البحѧѧث إلѧѧى التعѧѧرف علѧѧى الشخصیة الھامشیة لدى طالبات المرحلة المتوسطة. أما حدود البحث فتمثѧل بطالبѧات المرحلѧة المتوسѧطة فѧي محافظѧة دیѧالى (مركѧز مدینѧة بعقوبѧة) للعѧام الحѧالي ٢٠١٢ ـ ٢٠١٣ م . وقد استخدمت الباحثة المѧنھج الوصѧفي وتكونѧت عینѧة البحѧث مѧن (٢٠٠ (طالبѧة ، وقѧد أظھѧرت النتѧائج وجѧود شخصѧیة ھامشѧیة لطالبѧات المرحلѧة المتوسѧطة وأوصѧت الباحثѧة بوضѧع بѧرامج إرشѧادیة لتقلیѧل حѧدة الشخصѧیة الھامشѧیة ، واقترحѧت إجѧراء دراسة مقارنة للشخصیة الھامشیة بین البنین والبنات . Abstract : The importance of current research on the importance of adolescence that matched the middle school stage, at this stage teenagers are too desire to be in a world of adults before refueling experience to cope with various life situations that require them to prepare adequately before entering a new phase. Objective of this research is to identify the marginal personal with middle schoolers. The search limits represent intermediate by students in the province of Diyala (Baquba city center) for the current year 2012 2013. The researcher used the descriptive method consisted sample of 200 students, results showed a marginal figure for the students of the middle stage and researcher recommended developing outreach programs to mitigate personal marginal, and suggested a comparative study of the personality marginal between boys and girls